2020
DOI: 10.1590/interface.190634
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Burnout e fatores associados em profissionais da Estratégia Saúde da Família

Abstract: Este trabalho objetiva analisar presença de burnout e fatores relacionados em profissionais da Estratégia Saúde da Família. Trata-se de um estudo de delineamento transversal analítico, realizado entre fevereiro e abril de 2019. A amostra contou com 94 profissionais. Foi utilizado formulário com variáveis sociodemográficas, Escala Modo Enfrentamento de Problemas, Escala de Resiliência e Oldenburg Burnout Inventory. Intervalo de confiança de 95% foi calculado para cada variável. Em relação ao perfil de profissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 23 publications
0
6
0
14
Order By: Relevance
“…Soma-se a isso a falta de treinamento e, inclusive, a insuficiência ou indisponibilidade de equipamentos de proteção, mesmo nos serviços de terapia intensiva 28,29 . Esses são fatores que podem inclusive aumentar o risco de desenvolvimento de doenças psicossociais, como a SB, em que o indivíduo passa por um esgotamento físico, mental e emocional, levando-o a mudanças comportamentais que podem comprometer a sua vida enquanto ser humano e profissional 30,31 .…”
Section: Discussionunclassified
“…Soma-se a isso a falta de treinamento e, inclusive, a insuficiência ou indisponibilidade de equipamentos de proteção, mesmo nos serviços de terapia intensiva 28,29 . Esses são fatores que podem inclusive aumentar o risco de desenvolvimento de doenças psicossociais, como a SB, em que o indivíduo passa por um esgotamento físico, mental e emocional, levando-o a mudanças comportamentais que podem comprometer a sua vida enquanto ser humano e profissional 30,31 .…”
Section: Discussionunclassified
“…23 Unfortunately, coping with this health emergency operates under poor working conditions, 13,16,19 due to the scarcity of biosafety equipment, infection control systems, lack of recognition programs and work incentives, and finally physical and psychological abuse and discrimination by patients. 24 These factors impact their mental health states the study. This goes along with thinking about the known stressors of the work context that can be identified as psychosocial work factors.…”
Section: Resultsmentioning
confidence: 99%
“…The impact does not affect all countries in the same way in Brazil, for example, with a deficient health care system, economic, geographical, and social problems due to accessibility; poor infrastructure, lack of equipment, and working conditions. 14,24 Another study indicates that the inadequate management of health services generated by stress affects good performance, as well as influences the quality of care and consequently puts patient safety at risk, 29 while another states that COVID-19 brings the exposure of health personnel to physical, biological and psychological risks, without having the basic conditions to control, mitigate and cope with the serious and even irreversible consequences of the pandemic, so it can be considered an occupational disease due to the psychological consequences. 30 It is evident that this pandemic has serious psychosocial effects on health professionals, since they are directly linked to working conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Tomaz et al 15 identified high levels of burnout in ESF professionals, moderate scores in the factors that compose resilience, and low efficiency in the use of strategies to combat stressors. The study warns of the need to face the challenges related to ESF workers' health, including emotional support to professionals and the organization of a network to assist them in their daily work.…”
mentioning
confidence: 99%